Strategi Manajemen Inovasi Pembelajaran Berbasis Teknologi - Puspito Rini, Puput (Jurnal Inovasi dan Teknologi Pendidikan, 2024)
Technology-based learning innovation management is a field of study that integrates innovation management science, educational technology, and organizational strategies to design and evaluate the use of technology in encouraging effective and sustainable learning. This study aims to examine the management strategy of technology-based learning innovation through four dimensions, namely the effectiveness of technology implementation strategies, the role of artificial intelligence, the contribution of organizational digital capabilities, and the relevance of sectoral context in formulating a comprehensive and applicable strategy framework. The method used is Systematic